FGF21 as Modulator of Metabolism in Health and Disease - Tezze, Caterina; Romanello, Vanina; Sandri, Marco (Frontiers in Physiology, 2019)
Fibroblast growth factor 21 (FGF21) is a hormone that regulates important metabolic pathways. FGF21 is expressed in several metabolically active organs and acts on different tissues. The FGF21 action is complicated and debated because of the different sites of production and action. Striated muscles are plastic tissues that undergo adaptive changes of their structural or functional properties to meet different stresses and, recently, were found to be an important source of FGF21. The FGF21 expression and secretion from skeletal muscles happens during different physiological and pathological conditions such exercise or mitochondrial dysfunction both in mouse and humans. Here we discuss the recent findings that identify FG21 as a beneficial or detrimental cytokine that acts in autocrine or endocrine way to modulate cellular function, metabolism and senescence.